Asymmetric composite wound nanodressing with superhydrophilic/superhydrophobic alternate pattern for reducing blood loss and adhesion. (15th October 2021) - Long, Cai; Qing, Yongquan; Li, Songhe; Cui, Miao; Han, Mengxue; An, Kai; Long, Xiao; Liu, Chen; Liu, Changsheng
Abstract: Wound dressings are of great importance in trauma medicine. However, such dressings are poor in hemostatic effect, and they easily adhere to the wound skin, leading to their unsatisfactory effects for clinical application. Herein, we developed a new concept of creating an asymmetric composite wound nanodressing (ACWN) with unique structure consisting of superhydrophilic/superhydrophobic alternate inner layer and superhydrophobic outer layer. Compared to traditional hemostatic materials, our fabricated material consisted of integration of alternate micropattern wettability of the inner layer and the asymmetric wettability of the inner/outer layers into simple gauze. This ACWN was verified to overcome the challenge of reducing blood loss and simultaneously reducing adhesion based on the results of rat experiments both in in vivo and in vitro . Importantly, the resulting ACWN exhibited efficient blood absorption and clotting abilities on the zone of superhydrophilic inner layer. Moreover, the zone of superhydrophobic inner layer with blood repellency could avoid pain and secondary injuries caused by forced removal of dressings, and its outer layer could further prevent blood extravasation and reduce the risk of infection. Undoubtedly, this effective strategy provides new insight into the practical application of hemostatic materials.